Zengshengping improves lung cancer by regulating the intestinal barrier and intestinal microbiota - Sun, E.; Meng, Xiangqi; Kang, Zhaoxia; Gu, Huimin; Li, Mingyu; Tan, Xiaobin; Feng, Liang; Jia, Xiaobin (Frontiers in Pharmacology, 2023)
Lung cancer is a common malignant tumor in clinical practice, and its morbidity and mortality are in the forefront of malignant tumors. Radiotherapy, chemotherapy, and surgical treatment play an important role in the treatment of lung cancer, however, radiotherapy has many complications and even causes partial loss of function, the recurrence rate after surgical resection is high, and the toxic and side effects of chemotherapy drugs are strong. Traditional Chinese medicine has played a huge role in the prognosis and improvement of lung cancer, among them, Zengshengping (ZSP) has the effect of preventing and treating lung cancer. Based on the “gut-lung axis” and from the perspective of “treating the lung from the intestine”, the purpose of this study was to research the effect of Zengshengping on the intestinal physical, biological, and immune barriers, and explore its role in the prevention and treatment of lung cancer. The Lewis lung cancer and urethane-induced lung cancer models were established in C57BL/6 mice. The tumor, spleen, and thymus were weighed, and the inhibition rate, splenic and thymus indexes analyzed. Inflammatory factors and immunological indexes were detected by enzyme-linked immunosorbent assay. Collecting lung and colon tissues, hematoxylin and eosin staining was performed on lung, colon tissues to observe histopathological damage. Immunohistochemistry and Western blotting were carried out to detect tight junction protein expression in colon tissues and expression of Ki67 and p53 proteins in tumor tissues. Finally, the feces of mice were collected to investigate the changes in intestinal microbiota using 16SrDNA high-throughput sequencing technology. ZSP significantly reduced tumor weight and increased the splenic and thymus indexes. It decreased expression of Ki67 protein and increased expression of p53 protein. Compared with Model group, ZSP group reduced the serum levels of interleukin (IL)-1β, IL-6, tumor necrosis factor α (TNF-α), and ZSP group increased the concentration of secretory immunoglobulin A (sIgA) in the colon and the bronchoalveolar lavage fluid (BALF). ZSPH significantly increased the level of tight junction proteins such as ZO-1, Occludin and Claudin-1. Model group significantly reduced the relative abundance of Akkermansia (p < 0.05) and significantly promoted the amount of norank_f_Muribaculaceae, norank_f_Lachnospiraceae (p < 0.05) compared with that in the Normal group. However, ZSP groups increased in probiotic strains (Akkermansia) and decreased in pathogens (norank_f_Muribaculaceae, norank_f_Lachnospiraceae). Compared with the urethane-induced lung cancer mice, the results showed that ZSP significantly increased the diversity and richness of the intestinal microbiota in the Lewis lung cancer mice. ZSP played an important role in the prevention and treatment of lung cancer by enhancing immunity, protecting the intestinal mucosa and regulating the intestinal microbiota.